PENGEMBANGAN E-MODUL BERBASIS STEM UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI LIMBAH HASIL HEWANI - Destie Monikha Austriya Umbara (Jurnal Pendidikan, 2022)
The number of students who are able to achieve the Graduation Criteria in the subject of animal product processing production is only 22.5%. Problems regarding the limited facilities and completeness of the material caused the delivery of the material to be hampered. Through STEM-based e-modules, it can provide broader material and provide an overview between the material and the real world so that it is easier to understand. The purpose of this study was to determine the feasibility of STEM-based e-modules through expert validation and see if there were differences in learning outcomes between the control and experimental classes. The control class used PowerPoint as a learning resource and the experimental class used STEM-based e-modules. The development is carried out on the basic competence of analyzing waste from animal production. The research method used is ADDIE and Quasi-experimental. The sample consisted of 25 students of SMK majoring in Agribusiness Processing of Agricultural Products. Based on the results of the validation on the development of e-modules, the category "very feasible". In the application, there were differences in learning outcomes between the control and experimental classes. The experimental class got an average N-Gain score higher than the control class.